PENGGUNAAN ALOKASI DANA DESA DALAM MENUNJANG PEMBANGUNAN DI DESA KARYAMUKTI KECAMATAN MOOTILANGO KABUPATEN GORONTALO - Joice Machmud; Umar Sako; Erlin Yusuf Lapananda (Universitas Muhammadiyah Gorontalo, 2023)
This study aims to determine the extent of the use of village fund allocation (ADD) in supporting development in Karyamukti Village, Mootilango District, Gorontalo Regency. The research method used is a qualitative approach with a descriptive type of research. The results of the research obtained are: 1) The allocation of Village Funds (ADD) received by the Karyamukti Village Government, Mootilango District, Gorontalo Regency, is more directed at employee expenditures, Goods and Services expenditures and Capital Expenditures, 2) The use of ADD funds on employee expenditures to finance the fixed income of village heads and village officials, allowances for village heads and village officials as well as allowances for BPD and its members, 3) The use of ADD funds in the expenditure of goods and services is more directed at fulfilling administrative matters, monthly fixed costs as well as official travel and others, and 4) The use of ADD funds in development activities is completely unexplained because the funds received are only used up in 3 activities that are the focus of the budget.